Discrete Mathematics and Its Applications (SIE) - Rosen, Kenneth H.; Krithivasan, Kamala (New Delhi McGraw Hill Education, 2021)
Fulltext
Keywords: Mathematics; Computer science -- Mathematics; Logic, Symbolic and mathematical